2009
DOI: 10.1103/physrevb.80.014106
|View full text |Cite
|
Sign up to set email alerts
|

Verifying predictions of theL13crystal structure in Cd-Pt and Pd-Pt by exhaustive enumeration

Abstract: ͑2001͔͒ predicted a never-before-observed crystal structure in Ag-Pd. Recently, Curtarolo predicted the same structure to be stable in Pt-Cd and Pt-Pd ͓S. Curtarolo et al., CALPHAD: Comput. Coupling Phase Diagrams Thermochem. 29, 163 ͑2005͔͒. The predicted structure is unique in several ways. Though never seen in any other face-centered-cubic-based intermetallic binary compound or ordered alloy, it is relatively simple-it contains only four atoms per unit cell. Furthermore, the structure is the only one of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…For example, the prototype Pd 3 Ti 2 , reported only in the Pd-Ti system [36], also emerges as a calculated groundstate in the closely related systems Hf-Pd and Pt-Ti. In Hf-Pt, it appears as marginally stable, at 3meV/atom above the convex hull, in agreement with a very recent experimental study that identified the previously incorrectly character- [2,13,25,27,29,31]. ∆H are the formation enthalpies from the present study.…”
Section: High-throughput Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…For example, the prototype Pd 3 Ti 2 , reported only in the Pd-Ti system [36], also emerges as a calculated groundstate in the closely related systems Hf-Pd and Pt-Ti. In Hf-Pt, it appears as marginally stable, at 3meV/atom above the convex hull, in agreement with a very recent experimental study that identified the previously incorrectly character- [2,13,25,27,29,31]. ∆H are the formation enthalpies from the present study.…”
Section: High-throughput Resultssupporting
confidence: 92%
“…Indeed many recent studies present such calculations of PGM alloy structures . However, most of these studies consider a limited * E-mail address: stefano@duke.edu number of structures, at just a few stoichiometries of a single binary system or a few systems [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Some cluster expansion studies of specific binary systems include a larger set of structures, but limited to a single lattice type (usually, fcc) [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…We also find a few other compounds with unobserved prototypes (marked by a ? in Tables I, II, III, IV, V, and VI) previously uncovered in related HT studies [2,13,25,27,29,31].…”
Section: Methodsmentioning
confidence: 63%
“…In addition, the reader can prepare phase diagrams (as in Figs. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] linked to the appropriate structure URL locations. The Supplemental Material contains the whole set of geometrical and relaxed structures with ab initio total energies and formation enthalpies (see Ref.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation